Evaluation on envelope waveforms of velocity in common carotid artery: age-, gender- and regular exercise-related effect - Noor Azmi, Azran Azhim; Ueno, Akinori; Tanaka, Masato; Utsunomiya, Taniki; Akutagawa, Masatake; Obara, Shigeru; Tanaka, Hiroyuki; Kinouchi, Yohsuke (Springer Berlin Heidelberg, 2009)
The present study was aimed to examine the availability of the envelope waveforms of blood velocity and its indices in common carotid artery (CCA) as the parameter influenced by gender difference, aging and regular exercise. Evaluation of CCA blood velocity waveforms was performed in 202 healthy volunteers. Multivariate analysis was used to determine the relationship between the fixed factor and the outcome hemodynamic variables after adjustment for the related factors. Results showed a gender difference in velocity indices, except for peak systolic blood velocity. There was a general age-related decrease in flow velocities and change in the velocity waveform. The findings suggest that envelope waveform indices provide a more reliable evaluation by taken into account the impact of aging, gender, and regular exercise on CCA flow velocity. In conclusion, the normal blood velocity parameters in CCA are determined from a total of 202 healthy volunteers between the third and seventh age decade after adjustment for gender and exercise effects. Findings may contribute to improved means of healthcare monitoring and clinical evaluation.